Evaluation of persistent versus commercial nematode strains for management of Curculio caryae (Horn) and other weevils in pecan - Eddie K. Slusher; Elson Shields; Will Harges; Jermaine D. Perier; David Shapiro-Ilan (Biological Control)
Pecan weevil is a key pest of pecans. In addition, weevils such as Fuller rose beetle (FRB) and two-banded Japanese weevil (TJW) feed on pecan foliage and roots. Entomopathogenic nematodes (EPNs) have previously been shown to be effective tools for pecan weevil management. However, EPNs need frequent reapplication. Thus, there is a need to develop persistent strains of EPNs that can be applied less frequently and at lower rates. In this study, we compared two persistent strains of EPNs, NY01′ (Steinernema carpocapsae Weiser) and NY04′ (Steinernema feltiae Filipjev), against two commercial EPN strains, ScAll (S. carpocapsae) and SfSn (S. feltiae), in the lab and field. For the field study, the suppressive ability of each pair of EPNs on pecan weevil, FRB, and TJW was compared alongside a water only control. EPNs were only applied in the first year of the study (2022) and insect populations were monitored in 2022 and 2023. For the field study in Georgia, significantly fewer TJW were caught in trees treated with either nematode type in both study years. For the field study in Oklahoma, significantly fewer pecan weevils were caught in trees treated with commercial nematodes compared to the persistent nematodes and control in both study years. In lab trials, there was a lack of consistency in survival of the four strains. The results of this study indicate that commercial nematodes can have substantial carryover across two field seasons and can be applied at a significantly lower rate and still provide pest suppression.